PENDIDIKAN KARAKTER TERINTEGRASI DALAM PEMBELAJARAN IPA GUNA MENUMBUHKAN KEBIASAAN BERSIKAP ILMIAH (UPEJ Unnes Physics Education Journal, 2013)
In the midst of rapid global growth, increasingly complex and sophisticated, the principles of education to develop ethics, values and character of the students still must be held. Empowering learning science with a focus on the development of a scientific  attitude (responsibility, honesty, cooperation, self-confidence, curiosity, and creative) is an alternative way of integrated elements of character and increase student achievement. This aims of research to implement an integrated character education in learning science with Holistic learning model to cultivate scientific attitude and improve student achievement. Subjects were elementary school third grade students Patemon 01 Elementary School year 2012/2013. This research used classroom action research design that consist of three cycles. Data collected by using documentation, observation sheets, and test method. The results of data analysis showed an increase in scientific attitudes and student achievement. This proved that the integration of character education in learning science can be used as a scientific attitude acquisition, the noble value, and increasing student achievement.